CHARACTERIZATION PHENOTYPE AND GENETIC DISTANCE SOME OF THE NATIVE CHICKEN STRAINS IN JAMBI PROVINCE INDONESIA - Depison,; Gushairiyanto,; Irmaya, Dika (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Characterization is used to determine genetic quality which is used as a basis for consideration in selection and crossing. The research materials were Super Chicken, Bangkok, KUB, Sentul, Kampung and Merawang. Data including qualitative and quantitative. Descriptive and quantitative qualitative data used t-test, T2-Hotelling test and principal component analysis. Data processing using Minitab and MEGA-X program. The results showed that body weight, weight gain and body size of Super chickens were significantly different (P